2004
DOI: 10.1002/mrd.20195
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the nonreducing terminal β‐galactosyl residues of the neutral N‐linked carbohydrate chains of porcine zona pellucida glycoproteins in sperm–egg binding

Abstract: The zona pellucida (ZP) surrounding the mammalian oocyte is composed of three glycoprotein components (ZPA, ZPB, and ZPC). Mammalian sperm bind to carbohydrate chains of a ZP glycoprotein in the initial phase of fertilization. Sperm-ligand carbohydrate chains have been characterized in mouse, cow, and pig. In pigs, triantennary/tetraantennary neutral complex-type chains from ZPB/ZPC mixture possess stronger sperm-binding activity than those of biantennary chains (Kudo et al., 1998: Eur J Biochem 252:492-499). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…A feasible role for oviductal b-D-galactosidase would concern remodeling the ZP since b-galactosyl residues in the ZP oligosaccharides are involved in porcine sperm-egg binding (Yonezawa et al 2005). These authors showed that treatment with b-D-galactosidase and endo-b-D-galactosidase of isolated porcine ZPs reduced the number of sperm bound and inhibited the sperm penetration in treated oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A feasible role for oviductal b-D-galactosidase would concern remodeling the ZP since b-galactosyl residues in the ZP oligosaccharides are involved in porcine sperm-egg binding (Yonezawa et al 2005). These authors showed that treatment with b-D-galactosidase and endo-b-D-galactosidase of isolated porcine ZPs reduced the number of sperm bound and inhibited the sperm penetration in treated oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In both species, the biologically active carbohydrates are linked to the ZPB glycoprotein. The heteromultimeric complex of recombinant porcine ZPglycoproteins expressed in baculovirus-Sf9 insect cells carrying pauci-and high-mannose type glycans binds bovine but not porcine sperm (Yonezawa et al, 2005), indicating that in fact the binding event is dependent on the expression of specific carbohydrates. Despite the use of differing receptor-ligand systems, sperm are able to interact with the heterologous zona pellucida in vitro.…”
Section: Species-specificity Of Gamete-recognitionmentioning
confidence: 99%
“…The sperm-binding activity has been mapped to the neutral triand tetra-antennary complex N-glycans of ZPB expressing nonreducing terminal β-galactosyl residues (Kudo et al, 1998;Yonezawa et al, 2005). The request for polyvalency to achieve stable binding may be the reason that tri-and tetra-antennary glycans are shown to possess higher binding activity than the biantennary chains.…”
Section: Receptor-ligand Systems Involved In Primary Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, sperm that suffer AA due to interaction with SBG in the lumen of the isthmus at post-ovulatory stages of oestrus would keep SBG bound at their altered acrosomal membrane. Considering that ZP3α (Mr 55 kDa) binds to the acrosome region of acrosome-damaged or partially acrosome-reacted spermatozoa (Yonezawa et al, 2005), that Mr 55 kDa zona pellucida component exhibits Galβ1-3GalNac, as does SBG (Marini and Cabada, 2003), and that deglycosylation of Mr 55 kDa makes ZP unable to trigger acrosomal reaction, it is possible that SBG bound to AA sperm would block their interaction with ZP3α. Reduction of the number of sperm bound to the zona may serve to reduce the incidence of polyspermy (Hunter, 1993;Killian, 2004).…”
Section: Cellular Distribution Of Tyrosine-phosphorylated Proteins Upmentioning
confidence: 99%